Studien zum konvektiven Niederschlagsgeschehen im Lake Victoria Gebiet mit digitalen METEOSAT-Daten - Menz, Gunter; Bachmann, Matthias (ERDKUNDE, 1992)
Digital METEOSAT images represent a unique data base for for the study of temperature patterns and horizontal movements of convective cloud systems within the Inner Tropics of Eastern Africa. In the present paper, time series of calibrated METEOSAT images of Kenya are analysed for the period of March to May 1990 - the period of the long rains. The method applied has the following advantages in comparison to convectional studies: 1. Improvement of the understanding of the diurnal formation and circulation of cloud systems in the Lake Victoria area. 2. Differentiation of day- and night-rainfalls in relation to topography and surface coverage. 3. Calculation of rainfall maps for arbitrary time intervals.